2022
DOI: 10.3390/biomedicines10071499
|View full text |Cite
|
Sign up to set email alerts
|

Increased Oxidative Stress in Asthma—Relation to Inflammatory Blood and Lung Biomarkers and Airway Remodeling Indices

Abstract: Airway inflammation in asthma is related to increased reactive oxygen species generation, potentially leading to tissue injury and subsequent airway remodeling. We evaluated oxidative stress in peripheral blood from asthmatic subjects (n = 74) and matched controls (n = 65), using recently developed real-time monitoring of the protein hydroperoxide (HP) formation by the coumarin boronic acid (CBA) assay. We also investigated the relation of the systemic oxidative stress response in asthma to disease severity, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Studies on ex vivo models of obstructive airway disease have identified that oxidative stress, through its impact on mitochondrial function, drives airway inflammation and remodeling [ 76 , 77 , 78 ]. More specifically, in response to ozone stimulation, mitochondrial dysfunction triggers the development of airway inflammation and hyperresponsiveness [ 79 ].…”
Section: Relevant Sectionsmentioning
confidence: 99%
“…Studies on ex vivo models of obstructive airway disease have identified that oxidative stress, through its impact on mitochondrial function, drives airway inflammation and remodeling [ 76 , 77 , 78 ]. More specifically, in response to ozone stimulation, mitochondrial dysfunction triggers the development of airway inflammation and hyperresponsiveness [ 79 ].…”
Section: Relevant Sectionsmentioning
confidence: 99%
“…Damage to proteins, lipids and nucleic acid as a result of oxidative stress leads to pathological changes in airway epithelial cells, resulting in increased airway permeabili ty and hyperresponsiveness, as well as mucus production [25] (Figure 3).…”
Section: Ros In the Pathogenesis Of Asthmamentioning
confidence: 99%
“…Oxidative stress is caused by oxidative reactions that affect cells containing high levels of ROS ( 9 ). Since oxidative stress contributes to asthma severity ( 10 ), factors that reduce its severity should help prevent asthma. ROS are typically detoxified by antioxidant mechanisms such as those involving the enzymes superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx).…”
Section: Introductionmentioning
confidence: 99%